VÁLOGATOTT AFRIKAI TANULMÁNYOK BIEDERMANN ZSUZSÁNNA EMLÉKÉRE - Salih, Mohamed (Afrika Tanulmányok / Hungarian Journal of African Studies, 2025)
Mohamed Salih presented the following work: SELECTED AFRICAN STUDIES IN MEMORY OF ZSUZSÁNNA BIEDERMANN. EDITED BY JUDIT KISS AND ISTVÁN TARRÓSY. NEWCASTLE UPON TYNE: CAMBRIDGE SCHOLARS PUBLISHING, XIII + 345 PP, 2024.